Upaya Menggagas Pembelajaran Islami dalam Sistem Pendidikan di Aceh - A. Samad (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2016)
Aceh is one area in Indonesia given specificity by the central government to implement Islamic law, in other words the whole line of the Acehnese people must be based on Islamic Shari'a, good social life, economics, politics, and education. To realize that this law can really be implemented in the community one way is by education, therefore the education that takes place in Aceh must be based on Islamic values. The parties involved in the world of education must design a teaching system that is truly Islamic. Islamic Learning is learning that in accordance with Islamic law.